'Swift Rail'—funding local rail transit through smarter growth. Issue 6 (18th September 2016) - Harman, Reg; Falk, Nicholas
Abstract : Many medium-size cities suffer from severe traffic congestion and poor accessibility, limiting their potential to improve their economy, environment, and social equity. These problems could be addressed by creating high-quality transit linking such cities with suburban and other catchment areas through use of existing rail lines and abandoned former railway alignments. This concept, termed 'Swift Rail', would call for an innovative approach to local railway and transport development.